2014
DOI: 10.1021/ma5017693
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Mechanical Properties of a Poly(methyl methacrylate) Nanocomposite with Functionalized Graphene Sheets through Detailed Atomistic Simulations

Abstract: Recent experimental studies have demonstrated that the introduction of oxygen-containing functional groups in graphene sheets can greatly enhance the mechanical properties of their nanocomposites with polar polymers even at extremely low loadings. Motivated by these reports, we determine here the elastic constants of syndiotactic poly(methyl methacrylate) (sPMMA) at small wt % loadings of graphene sheets through atomistic modeling. To carry out a comparative study of the effect of graphene functionalization on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 67 publications
(128 reference statements)
6
76
0
Order By: Relevance
“…Many simulation and experimental studies [1,[6][7][8][9][10][11][12][13][14][15][16][17][18][19] explore the influence of the chemical functionalization of graphene on the various properties of the nanocomposites. For example, Konatham et al [14] presented results based on atomistic Molecular Dynamics simulations combined with coarse grained Monte Carlo simulations, focused on graphene sheets dispersed in n-octane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many simulation and experimental studies [1,[6][7][8][9][10][11][12][13][14][15][16][17][18][19] explore the influence of the chemical functionalization of graphene on the various properties of the nanocomposites. For example, Konatham et al [14] presented results based on atomistic Molecular Dynamics simulations combined with coarse grained Monte Carlo simulations, focused on graphene sheets dispersed in n-octane.…”
Section: Introductionmentioning
confidence: 99%
“…They also mention the effect of the size of the graphene sheets, though their atomistic simulations are limited to rather small sheets. More recently Skoutzos et al [15] presented results for syndiotactic poly(methyl methacrylate)/graphene nanocompostites, based on atomistic Molecular Dynamics simulations. They found that the introduction of oxygen-containing functional groups in graphene sheets leads to a great enhancement of the mechanical properties of the hybrid system, even at extremely low loading.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum density appears somewhere between 0.4 and 0.5 nm from the nanofiller that is a common observation for polymer/G systems. This is mainly due to the adsorption of polymer by the nanofiller . Note that since polymer chains embedded the nanofiller in all directions ( x , y , and z ) in such a way that the box lateral dimension is slightly larger than the nanofiller surface, the density does not reach 0 at z = 0, for better imagination see Figure .…”
Section: Resultsmentioning
confidence: 98%
“…Recently, Skountzos et al predicted the mechanical properties of syndiotactic PMMA (sPMMA) with varying weight fraction of pristine and functionalized graphene sheets (FGS). Their simulations showed a tremendous increase in the elastic constants (Young's modulus by ~74%, bulk modulus by ~19%, and shear modulus by ~83%), with the FGS.…”
Section: Atomistic Simulations To Characterize the Graphene‐polymer Nmentioning
confidence: 99%